Strategic Public Procurement: Facilitating Sustainable Development in Ukraine - Malolitneva, Vesta; Dzhabrailov, Ruslan (European Journal of Sustainable Development, 2019)
New benchmarks for world development were approved at the UN Summit in 2015, namely 17 Sustainable Development Goals. Ukraine, like other UN member states, has joined the global process of ensuring sustainable development. This requires conceptual changes in all spheres of life. Public procurement is considered as one of the most powerful tools for solving social, environmental and economic challenges facing the world. The article is dedicated to the role of sustainable public procurement and substantiation of ways of changing the conceptual approach to procurement in order to achieve the goals of sustainable development in Ukraine. Based on the analysis of foreign experience, it is proposed to change the approach to public procurement in Ukraine in such a way as to emphasize not only reduction of costs and saving of public funds but also the support of the long-term goals of the state. Keywords: public procurement, sustainable development, sustainable public procurement, “horizontal” objectives, green public procurement, socially responsible public procurement.